Towards Industry 4.0: Innovation of Digital-Based Academic Administration System in Islamic Religious Universities - Hijrawati Usman; Sahraini Sahraini; Munir Yusuf (STAI Hubbulwathan Duri, 2024)
The Industry 4.0 era demands digitalization in all fields, including public services in the higher education sector. This research aims to develop a digital-based academic administration service system. The research was conducted at the Faculty of Tarbiyah and Keguruan Sciences, Institut Agama Islam Negeri Palopo. The development method used was Rapid Application Development (RAD), with stages of requirements planning, system design, development and feedback collection, and product implementation. This research involved staff or education personnel and web developer experts. Data were collected through observation and validation questionnaires and analyzed descriptively using percentage techniques to determine validity. Product validity was tested by expert web developers through analysis using the Aiken V formula. This research provides an important understanding of the importance of digitalization in improving the efficiency and quality of academic administration services in the digital era. The results of this study provide a significant contribution to developing a digital-based academic administration service system and can be a foundation for further research and development in the future. This research significantly impacts academic administration practice by contributing to a digital-based service system. These findings can be the basis for further research and development on optimizing academic administration services in the digital era.